The effects of 4 weeks of jump training on landing knee valgus and crossover hop performance in female basketball players - Herrington, L. (The Journal of Strength and Conditioning Research, 2010)
Female basketball players would appear particularly prone to knee injuries. These injuries have been associated with the nature of the sport, but more specifically with the particular movement strategies adopted. A valgus or abducted position of the knee on landing has been reported to be associated with a number of different knee injuries. Jump-training programs have been reported to improve both landing knee valgus and functional performance. The majority of the jump-training programs have been of 6 weeks' duration, 3 sessions per week often lasting up to 1 hour. For most sports coaches, team conditioners, and athletes, this duration and program length is not acceptable. The aim of this study was to assess if an abridged jump-training program could have similar effects to those previously reported. Fifteen female basketball players had their knee valgus angles assessed during 2 landing tasks, drop jump landing, and when undertaking a jump shot and along with crossover hop distance before and after a progressive jump-training program. The jump-training program lasted 4 weeks, 3 times per week, each session lasting 15 minutes. After training, crossover hop distance showed an average percentage improvement on distance jumped of 73.6% (p = 0.001); the drop jump knee valgus angle in the left leg on average was reduced by 9.8° (p = 0.002), right leg reduced by 12.3° (p = 0.0001); during the jump shot, the knee valgus angle in the left leg showed a mean reduction of 4.5° (p = 0.035), and the right leg was reduced by 4.3° (p = 0.01). The study undertaken achieved comparable results to those previously reported with an abridged program over considerably shortened session duration and training period.